Nanocomposite catalysts producing durable, super-black carbon nanotube systems: applications in solar thermal harvesting - Panagiotopoulos, Nikolaos T.; Diamanti, Evmorfia K.; Baikousi, Maria; Kordatos, Evangelos; Matikas, Theodore E.; Gournis, Dimitrios; Patsalas, Panos; Koutsokeras, Loukas E. (My University, 2012)
A novel two-step approach for preparing carbon nanotube (CNT) systems, exhibiting an extraordinary combination of functional properties, is presented. It is based upon nanocomposite films consisting of metal (Me = Ni, Fe, Mo, Sn) nanoparticles embedded into diamond-like carbon (DLC). The main concept behind this approach is that DLC inhibits the growth of Me, resulting in the formation of small nanospheres instead of layers or extended grains. In the second step, DLC:Me substrates were used as catalyst templates for the growth of CNTs by the thermal chemical vapor deposition (T-CVD) process. X-ray photoelectron spectroscopy (XPS) has shown that at the T-CVD temperature of 700 C DLC is completely graphitized and NiC is formed, making DLC:Ni a very effective catalyst for CNT growth. The catalyst layers and the CNT systems have been characterized with a wide range of analytical techniques such as Auger electron spectroscopy and X-ray photoelectron spectroscopy (AES/XPS), X-ray diffraction, reflectivity and scattering, Raman spectroscopy, scanning electron microscopy, atomic force microscopy, and optical and electrical testing. The produced CNTs are of excellent quality, without needing any further purification, durable, firmly attached to the substrate, and of varying morphology depending on the density of catalyst nanoparticles. The produced CNTs exhibit exceptional properties, such as super-hydrophobic surfaces (contact angle up to 165) and exceptionally low optical reflection (reflectivity <10-4) in the entirety of the visible range. The combination of the functional properties makes these CNT systems promising candidates for solar thermal harvesting, as it is demonstrated by solar simulation experiments
Keywords: Materials science; Engineering; Catalysts; Carbon; Nanotubes; Chemical vapor deposition; Light absorption; Nanocomposites; Pulsed laser deposition